Infection of Plasmodium knowlesi Malaria in Human - Asmara, I Gede Yasa (Jurnal Penyakit Dalam Indonesia, 2018)
Plasmodium knowlesi (P. knowlesi) has been recognised as the fifth of malaria infections in human after P. vivax, P. falciparum, P. malariae and P. ovale. Epidemiology and clinical features of the disease have much been discussed only in several literatures since the incidence increased in Kapit Division, Sarawak, Malaysia in 2004. A large-scale research investigating real incidence of the infection in South East Asia is important. Because of rapid life cycle, the number of parasite in the blood can increase significantly, result in potential severe malaria. Pathophysiology aspect of the disease has not been clear yet, particularly on how severe malaria can be occurred as similar as in P. falciparum infections. Early detection using moleculer technique is the gold standar of the diagnosis of knowlesi malaria. Although P. knowlesi infection is still sensitive to many anti-malaria drugs, prompt treatment is crucial since the infection might deteriorate fast.